A thermal-electrochemical-mechanical coupled model based on non-equilibrium thermodynamics of Li-ion batteries. (25th November 2022) - Jiang, Wenjuan; Zhou, Qi; Lu, Feng; Chen, Yufang; Ma, Zengsheng
Abstract: According to non-equilibrium thermodynamics in Li-ion batteries (LIBs), the complicated coupling relations exist among the electric flux, ion flux, heat flux and so on. In this paper, we propose a thermal-electrochemical-mechanical coupled model (TECM model) which could predict capacity loss, concentration evolution, thermal runaway and mechanical degradation by considering the thermal diffusion, thermoelectric, Dufour effects, etc. The correlation between prediction difference and discharging rate is further studied. The results show that TECM model is more suitable for electrical prediction under variable temperature conditions and the thermal prediction accuracy is higher, which is beneficial to thermal management. Also, TECM model can describe the multiple physics fields in one calculation. This model provides an approach to investigate the thermal, electrochemical and mechanical behaviors in LIBs. Highlights: An improved coupled model considers electrochemical, thermal, and mechanical filed. Rigorous derivation of flux-force coupling equations based on non-equilibrium thermodynamics. Non-isothermal electrochemical prediction models using thermal coupling. Higher predicted temperature for more efficient thermal management simulation.